Determinants of user experience and perception of educational quality in Peruvian university institutions: A structural equation modeling analysis - Urribarri, Africa Calanchez; Heros, Claudio Huamán De Los; Castillo, Angélica María Becerra (International Journal of Innovative Research and Scientific Studies, 2025)
This research aims to analyze the impact of curricular quality, academic staff competencies, infrastructure, and brand recognition on user experience and perceptions of educational quality in private universities in Peru. A quantitative study with a causal correlational design was conducted. Data were collected from 872 students from the Business School of a private university in Metropolitan Lima, using convenience sampling. The analysis employed structural equation modeling (SEM) with Smart PLS. Results indicate significant positive relationships between curricular quality and user experience (β = 0.236, p < 0.001) and perception of educational quality (β = 0.348, p < 0.001). Academic staff competencies strongly influence curricular effectiveness (β = 0.731, p < 0.001). Infrastructure showed significant effects on brand identification (β = 0.547, p < 0.001) and perception of educational quality (β = 0.377, p < 0.001). The study demonstrates that curricular quality, academic staff competencies, and infrastructure are key determinants of user experience and perception of educational quality in Peruvian universities. Educational institutions should prioritize investments in curriculum development, faculty professional development, and infrastructure improvement to enhance the student experience and perceived educational quality. These factors are crucial to building strong brand identification and maintaining a competitive advantage in higher education.